A Time‐Resolved Paleomagnetic Record of Main Group Pallasites: Evidence for a Large‐Cored, Thin‐Mantled Parent Body. Issue 7 (22nd July 2021) - Nichols, Claire I. O.; Bryson, James F. J.; Cottrell, Rory D.; Fu, Roger R.; Harrison, Richard J.; Herrero‐Albillos, Julia; Kronast, Florian; Tarduno, John A.; Weiss, Benjamin P.
Abstract: Several paleomagnetic studies have been conducted on five Main Group pallasites: Brenham, Marjalahti, Springwater, Imilac, and Esquel. These pallasites have distinct cooling histories, meaning that their paleomagnetic records may have been acquired at different times during the thermal evolution of their parent body. Here, we compile new and existing data to present the most complete time‐resolved paleomagnetic record for a planetesimal, which includes a period of quiescence prior to core solidification as well as dynamo activity generated by compositional convection during core solidification. We present new paleomagnetic data for the Springwater pallasite, which constrains the timing of core solidification. Our results suggest that in order to generate the observed strong paleointensities (∼65–95 μT), the pallasites must have been relatively close to the dynamo source. Our thermal and dynamo models predict that the Main Group pallasites originate from a planetesimal with a large core (>200 km) and a thin mantle (<70 km). Plain Language Summary: We have studied five pallasite meteorites which are composed of a green mineral called olivine surrounded by iron–nickel metal. These meteorites are all thought to originate from the same parent asteroid. We have measured the magnetism of these meteorites and recovered information about the magnetic fields they experienced when they initially formed and cooled. Our magnetic measurements show that the parent asteroid generated its own magnetic field, suggesting that the asteroid had a metallic core that was vigorously convecting. We find that our results are best explained by the parent asteroid having a large metal core and a thin rocky shell. Key Points: We present the most complete time‐resolved paleointensity record for five Main Group (MG) pallasites Paleointensities require the MG pallasites to have formed in a thin mantle overlying a large metallic core The MG pallasites could have originated from a parent body with a similar structure to the asteroid (16) Psyche